The effects of instructional self-talk on quiet eye duration and golf putting performance - Sarig, Yonatan (2017)
Yonatan Sarig, 2017. The Effects of Instructional Self-Talk on Quiet Eye Duration and Performance. Faculty of Sports and Health Science. University of Jyväskylä. Master’s thesis, 63p. While the literature on the effects of instructional self-talk is comprehensive, a somewhat under-investigated subject is the underlying mechanisms of instructional self-talk. As of late, the trend has been shifted towards researching what are the motivational and attentional constructs at the base of self-talk. Potentially, one such attentional construct is the quiet eye; the final gaze fixation on a target before the execution of task-oriented movement. Since the duration of the quiet eye is found to be associated with better performance, and interventions aimed at prolonging the quiet eye are always sought after, the aim of this study was to investigate whether instructional self-talk can prolong the quiet eye duration and thus, improve performance. For this purpose, 30 participants (M = 24.37, SD = 4.99) that were novices in golf putting were recruited. The participants took part in a golf putting trial, while half of them underwent a short-term instructional self-talk training using dart throwing. The quiet eye duration was measured using a SensoMotoric Instruments (SMI) eye tracker while performance was measured using the index of putting proficiency. Results showed that instructional self-talk had a positive effect on quiet eye duration and performance. However, no correlation between quiet eye duration and performance. The results indicate that quiet eye is a possible attentional mechanism of self-talk and might be used in quiet eye training.